T cell phenotype in paediatric heart transplant recipients. (16th December 2020) - Mengrelis, Konstantinos; Kucera, Filip; Shahid, Nadia; Watt, Eleanor; Ross, Susan; Lau, Ching‐In; Adams, Stuart; Gilmour, Kimberly; Pils, Dietmar; Crompton, Tessa; Burch, Michael; Davies, E. Graham
Abstract: Paediatric heart transplantation recipients suffer an increased incidence of infectious, autoimmune and allergic problems. The relative roles of thymus excision and immunosuppressive treatments in contributing to these sequelae are not clear. We compared the immunological phenotypes of 25 heart transplant recipients (Tx), 10 children who underwent thymus excision during non‐transplantation cardiac surgery (TE) and 25 age range–matched controls, in two age bands: 1‐9 and 10‐16 years. Significant differences from controls were seen mainly in the younger age band with Tx showing lower CD3 and CD4 cell counts whilst TE showed lower CD8 cell counts. Naïve T cell and recent thymic emigrant proportions and counts were significantly lower than controls in both groups in the lower age band. T cell recombination excision circle (TREC) levels were lower than controls in both groups in both age bands. There were no differences in regulatory T cells, but in those undergoing thymus excision in infancy, their proportions were higher in TE than Tx, a possible direct effect of immunosuppression. T cell receptor V beta spectratyping showed fewer peaks in both groups than in controls (predominantly in the older age band). Thymus excision in infancy was associated with lower CD8 cell counts and higher proportions of Tregs in TE compared to Tx. These data are consistent with thymus excision, particularly in infancy, being the most important influence on immunological phenotype after heart transplantation.